Tonsillectomy and/or adenoidectomy improves macular microcirculation in children with obstructive sleep apnea - Zhen Xue; Bangtao Yao; Yao Yang; Li Yin (Scientific Reports)
Abstract This study aims to observe the changes in macular microcirculation before and after tonsil and/or adenoid surgery in children diagnosed with obstructive sleep apnea (OSA). Pediatric patients with OSA who underwent tonsillectomy and/or adenoidectomy at the Department of Otorhinolaryngology, the Affiliated Jiangning Hospital with Nanjing Medical University, from July 2019 to December 2023, were included in the OSA group (n = 100). A control group consisting of normal children who underwent physical examinations at the ophthalmology clinic was also selected (n = 50). OSA-18 scale, and optical coherence tomography angiography (OCTA) were conducted. The study focused on the changes in the superficial capillary plexus (SCP), including vascular length density (VLD), vascular perfusion density (VPD), and the foveal avascular zone (FAZ) within the central concave region of the macula. (1) VLD1, VLD2, VPD1, and VPD2 exhibited significantly lower values in the macular area of children in the OSA group compared to the control group (P < 0.05). In contrast, VLD3, VLD4, VPD3, VPD4, and FAZ did not show statistically significant differences between the two groups (P > 0.05). (2) Postoperative OSA-18 scores in children with OSA were significantly lower than preoperative scores (P < 0.05). Additionally, postoperative VLD1, VLD2, VPD1, and VPD2 were significantly elevated in children with OSA (P < 0.05), while no statistically significant differences were observed for the remaining indices before and after surgery (P > 0.05). (3) There were no statistically significant differences across all indices between the OSA group at 6 months postoperatively and the control group (P > 0.05). Tonsillectomy and/or adenoidectomy may enhance macular microcirculation, potentially aiding in the prevention of fundus complications. OCTA could serve as a supplementary tool for the early assessment of surgical indications in pediatric cases of OSA.